1994
DOI: 10.1002/1097-0142(19940201)73:3<580::aid-cncr2820730314>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Localization of tumor-reactive lymph node lymphocytes in vivo using radiolabeled monoclonal antibody

Abstract: Background. Lymph node lymphocytes vary in their responsiveness to tumor. A technique has been developed that uses radiolabeled monoclonal antibody (MoAb) against the tumor‐associated mucin, TAG‐72, and a gamma‐detecting probe by which lymph nodes containing microscopic tumor and/or shed TAG‐72 can be identified in vivo. The immunologic characteristics of these lymph nodes were examined. Methods. Patients with colon cancer received 125I‐labeled MoAb CC49 by intravenous injection preoperatively. During laparoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 11 publications
0
10
1
Order By: Relevance
“…17 Mechanically disaggregated samples of tumor tissue were placed into culture for 48 hours (standardized to 10 6 cells) in modified AIM V. After 48 hours, they were cultured with 100 IU/mL of human recombinant IL-2 (Cetus, Emeryville, CA) for 7-10 days. Tumor cells and DCs were then separated by brief (20-minute) centrifugation on a discontinuous Percoll gradient.…”
Section: Recovery Of Cells From Injected Tumorsmentioning
confidence: 99%
“…17 Mechanically disaggregated samples of tumor tissue were placed into culture for 48 hours (standardized to 10 6 cells) in modified AIM V. After 48 hours, they were cultured with 100 IU/mL of human recombinant IL-2 (Cetus, Emeryville, CA) for 7-10 days. Tumor cells and DCs were then separated by brief (20-minute) centrifugation on a discontinuous Percoll gradient.…”
Section: Recovery Of Cells From Injected Tumorsmentioning
confidence: 99%
“…This may be due to the innate difference between the two procedures and to the denaturation of cross-linking proteins during formalin fixation. Background radioactivity in vivo may be due to binding of probe to membrane CEA on nontumor cells (Triozzi et al 1994), freely circulating agent, and dissociated radionuclides. Since we found that immunostaining was weak or nonexistent in organs without tumor cells, the first type of background radioactivity was not detected in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In this technique, 125 I-labeled CC49, a murine monoclonal antibody that targets the tumor associated antigen TAG-72, 36 is injected pre-operatively and at the time of laparotomy, a hand-held radiation detecting probe 37 is used to identify lymph nodes containing this antigen. 38 Interestingly, this technique can identify grossly tumor-free lymph nodes which contain lymphocytes that proliferate specifically in response to autologous tumor cells, allogeneic TAG-72 ϩ tumor cells, and soluble mucin possessing the TAG-72 epitope. 38,39 These lymphocytes secrete cytokines and are non-cytolytic.…”
Section: Adoptive Cellular Immunotherapymentioning
confidence: 99%
“…38 Interestingly, this technique can identify grossly tumor-free lymph nodes which contain lymphocytes that proliferate specifically in response to autologous tumor cells, allogeneic TAG-72 ϩ tumor cells, and soluble mucin possessing the TAG-72 epitope. 38,39 These lymphocytes secrete cytokines and are non-cytolytic. A phase I study in patients with unresectable metastatic colorectal cancer has been performed in which lymphocytes derived from resected, RIGS-localized lymph nodes were cultured ex vivo and reinfused as activated cell therapy (ACT).…”
Section: Adoptive Cellular Immunotherapymentioning
confidence: 99%